Effect of the Novel BKCa Channel Opener LDD175 on the Modulation of Corporal Smooth Muscle Tone. (10th November 2014) - Sung, Hyun Hwan; Choo, Seol Ho; Han, Deok Hyun; Chae, Mee Ree; Kang, Su Jeong; Park, Chul‐Seung; So, Insuk; Park, Jong Kwan; Lee, Sung Won
Abstract Introduction The BKCa channel has been reported to play an important role in erectile function. Recently, novel BKCa channel activator, LDD175, was introduced. Aim This study aims to investigate whether LDD175 relaxes corporal smooth muscle (CSM) via BKCa channel activation. Methods After isolation of CSM strip from a male rabbit model, contraction studies using organ bath was performed. Isolating human tissue and cell cultures, electrophysiological studies were done via whole‐cell patch‐clamp recording. Main Outcome Measures Vasodilatory effects of LDD175 were evaluated by cumulative addition ranging from 10−7 to 10−4 M in corpus cavernosal strips after precontraction with 10−5 M phenylephrine via organ bath system. Using cultured human CSM cells, patch‐clamp recording was performed. Erectile function was measured by in vivo rat cavernous nerve stimulation. Results LDD175 caused an endothelium‐independent relaxation of corporal tissues, and this effect was abolished by pretreatment with iberiotoxin. The relaxation effect of 10−4 M LDD175 was greater than that of 10−6 M udenafil (54.0 ± 3.1% vs. 34.5 ± 3.9%, P < 0.05); 10−5 M LDD175 with 10−6 M udenafil caused a greater relaxation effect on strips than 10−5 M LDD175 or 10−6 M udenafil alone (50.7%, 34.1%, vs. 20.7%, respectively, P < 0.001). In patch‐clamp recordings, LDD175 increased K+ currents in a dose‐dependent manner, and washout of LDD175 or the addition of iberiotoxin fully reversed the increase. Intravenous LDD175 improved erectile function measured by area under the curve (AUC) of the intracavernosal pressure (ICP)/arterial blood pressure (ABP) ratio (1, 612.1 ± 135.6 vs. 1, 093.7 ± 123.1, P < 0.05). There was no difference between 10 mg/kg LDD175 and 1 mg/kg udenafil regarding maximal ICP, maximal ICP/ABP ratio, and the AUC of the ICP/ABP ratio (P > 0.05). Conclusions LDD175 leads to an endothelium‐independent relaxation of erectile tissue, primarily through the opening of BKCa channels. The results suggest that LDD175 might be a new candidate treatment for erectile dysfunction. Sung HH, Choo SH, Han DH, Chae MR, Kang SJ, Park C‐S, So I, Park JK, and Lee SW. Effect of the novel BKCa channel opener LDD175 on the modulation of corporal smooth muscle tone. J Sex Med 2015;12:29–38.